The Scandinavian Fantasy: The Sources of Intergenerational Mobility in Denmark and the U.S. - Rasmus Landersø; James J. Heckman (Institute for the Study of Labor (IZA), 2016)
This paper examines the sources of differences in social mobility between the U.S. and Denmark. Measured by income mobility, Denmark is a more mobile society, but not when measured by educational mobility. There are pronounced nonlinearities in income and educational mobility in both countries. Greater Danish income mobility is largely a consequence of redistributional tax, transfer, and wage compression policies. While Danish social policies for children produce more favorable cognitive test scores for disadvantaged children, these do not translate into more favorable educational outcomes, partly because of disincentives to acquire education arising from the redistributional policies that increase income mobility.
Keywords: I32; I28; I24; P51; 330; social mobility; education; inequality; comparative analysis of systems